2017
DOI: 10.4025/jphyseduc.v28i1.2820
|View full text |Cite
|
Sign up to set email alerts
|

Resistence Exercise Improves Anxiety and Depression in Middle- Age Women

Abstract: RESUMOO estudo comparou níveis de ansiedade e depressão de mulheres treinadas em exercício resistido e de sedentárias. Quarenta mulheres, 20 treinadas (GT) e 20 não treinadas (GC), (GT=56,9±6,6 anos; 27,3±4,8kg/m 2 ), (GC=51,5±5,0 anos; 27,0±7,7 kg/m 2 ) participaram do estudo. As participantes responderam a escala HAD com 14 questões relacionadas aos níveis de ansiedade e depressão. O GC apresentou escores mais elevados de depressão e ansiedade que o GT. Os resultados para ansiedade (GT=5,2±2,7; GC=9,5±4,0) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…The study concluded that there was improvement in anxiety-trait levels ( p = 0.0048) and state anxiety ( p = 0.0359) in the exercise group. Similar evidence can be found in the study of Araújo et al (2). Although the study was done with healthy, middle-aged women, the results are positive.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study concluded that there was improvement in anxiety-trait levels ( p = 0.0048) and state anxiety ( p = 0.0359) in the exercise group. Similar evidence can be found in the study of Araújo et al (2). Although the study was done with healthy, middle-aged women, the results are positive.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have demonstrated the positive effects of RT on anxiety in middle-aged women (1,2). There is evidence that physical exercise is a promising intervention among nonpharmacological actions to manage fatigue, QOL, and anxiety in patients with cancer or BCS.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisa brasileira 33 e islandesa 34 observaram que a prática de exercícios físicos resistido na meia idade reduziram sintomas de depressão e ansiedade. Portanto, o sedentarismo pode estar associado à ausência de sucesso na terapêutica em saúde mental do grupo pesquisado.…”
Section: Discussionunclassified
“…This fact is possibly due to the lack of social support for the practice of physical activities. (ARAÚJO et al, 2017;CHANG et al, 2016;AGOSTINHO et al, 2020).…”
Section: )mentioning
confidence: 99%